The law of nines - Goodkind, Terry (New York : G.P. Putnam's Sons, 2009)
Turning twenty-seven may be terrifying for some, but for Alex, a struggling artist living in the midwestern United States, it is cataclysmic. Inheriting a huge expanse of land should have made him a rich and happy man; but something about this birthday, his name, and the beautiful woman whose life he just saved, has suddenly made him--and everyone he loves--into a target--target for extreme and uncompromising violence.
Keywords: Artists -- Nebraska -- Fiction; Legacies -- Fiction